Mixed Reality Based User Acceptance Measurement on Primary School Age Children (Case Study: Introduction to Indonesian Native Fauna) - Dimas Wahyu Wibowo; Muhammad Shulhan Khairy; Septian Enggar Sukmana (Universitas Dian Nuswantoro and IndoCEISS, 2022)
One aspect of learning media technology sustainability is the level of user acceptance of the learning media itself. It is related to the user loyalty or willingness to continuously use the learning media application. For primary school age children, analyzing the level of acceptance of learning media using the unified theory of acceptance and use of technology (UTAUT) is challenging. In its application, the formulation of the questions is carried out in a simple way therefore children can understand each meaning of the questions. In this study, the object of technology used is a mixed reality-based learning application, which contains introduction to Indonesia Native fauna material. To ensure that the inter-view questions meet the children’s psychological, the reliability and validity measure were taken as the initial step. Secondly, hypothesis testing was carried out to analyze the children behavioral intentions based on the variables contained in UTAUT. The results of this study indicate that students do not find difficulties in using this mixed reality-based learning media application, both on the technical and psychological (techno-stress) sides.